Knockdown of circ-PRKCH alleviates IL-1β-treated chondrocyte cell phenotypic changes through modulating miR-502-5p/ADAMTS5 axis - Zhongxing Liu; Jian Cao; Limin Zhang; Jinlong Li; Tinghan Yan; Peng Zhou; Sidi Zhang (Taylor & Francis Group, 2022)
Background Osteoarthritis (OA) is a common joint disease characterized by progressive cartilage degradation. Circular RNAs (circRNAs) are involved in the initiation and development of OA. This study aimed to explore the potential role and mechanism of circRNA protein kinase C eta (circ-PRKCH) in OA. Methods A total of 30 cartilage specimens were collected from OA patients or normal subjects. Human chondrocytes (CHON-001) were stimulated with interleukin-1β (IL-1β) to establish an in vitro OA model. The expression levels of circ-PRKCH, microRNA-502-5p (miR-502-5p) and circ-PRKCH or A disintegrin and metalloproteases metallopeptidase with thrombospondin type 1 motif 5 (ADAMTS5) in cartilage specimens and IL-1β-treated chondrocytes were detected by quantitative real-time PCR or Western blot, and their correlation in OA cartilage specimens was analysed by Spearman's correlation coefficient. The targeted relationship between miR-502-5p and circ-PRKCH or ADAMTS5 was verified by dual-luciferase reporter assay and RNA Immunoprecipitation (RIP) assay. Cell Counting Kit-8 (CCK-8), 5-Ethynyl-2'-deoxyuridine (EDU), flow cytometry, wound healing and enzyme-linked immunosorbent assay (ELISA) assays were applied to evaluate cell proliferation, apoptosis, migration and inflammatory response in IL-1β-treated chondrocytes. Exosomes were identified by transmission electron microscope (TEM) and Western blot. Results Circ-PRKCH and ADAMTS5 expression levels were up-regulated, while miR-502-5p expression was down-regulated in OA cartilage tissues and IL-1β-treated chondrocytes. Depletion of circ-PRKCH relieved IL-1β-treated chondrocyte cell phenotypic changes by promoting cell proliferation and migration, as well as inhibiting apoptosis and inflammatory response. Mechanically, circ-PRKCH acted as a sponge for miR-502-5p to regulate ADAMTS5 expression, thereby contributing to IL-1β-treated chondrocyte cell phenotypic changes. Moreover, exosomes derived from IL-1β-treated chondrocytes could transfer circ-PRKCH across cells. Conclusion Circ-PRKCH contributed to IL-1β-treated cell phenotypic changes in chondrocytes via modulating miR-502-5p/ADAMTS5 pathway, which might provide a promising biomarker for OA treatment.